2021
DOI: 10.1007/s00066-021-01891-1
|View full text |Cite
|
Sign up to set email alerts
|

Kardiale stereotaktische Strahlentherapie induziert eine Umprogrammierung des elektrischen Reizleitungssystems

Abstract: Hintergrund Die kardiale stereotaktische Strahlentherapie (cSBRT), auch Herzradiochirurgie oder Radioablation (RA) genannt, hat in der Behandlung von Patienten mit refraktären ventrikulären Tachykardien (VT) einen deutlichen therapeutischen Effekt im Sinne einer Reduktion der VT-Ereignisse und assoziierter Auslösungen der Implantierbarer-Kardioverter-Defibrillator(ICD)-Interventionen (Überstimulation, Schock) erzielt. Der für die cSBRT bislang postulierte Wirkmechanismus der radiogenen Fibrose erklärt jedoch n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Hence, one of the major WP 2 of the STOPSTORM consortium project is designated to the harmonization of TV definition as this is currently the largest uncertainty of STAR. 10 , 13 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, one of the major WP 2 of the STOPSTORM consortium project is designated to the harmonization of TV definition as this is currently the largest uncertainty of STAR. 10 , 13 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Almost all centres use a single dose of 25 Gy at the time, while some centres began looking into dose modification based on recent findings from radiation biology studies. 14 , 15 , 17 However, the methods of planning margins, dose prescription, target coverage, dose (in)homogeneity, and treatment duration vary greatly. Inconsistent documentation further complicates comparability between institutions and even systems.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al. found increases of Na v 1.5 and Cx43 and concluded that radiation-induced reprogramming of cardiac conduction is a potential treatment strategy [ 7 , 8 ]. Initial clinical evidence showed changes of ventricular conduction velocity in myocardium subject to 25 Gy or additional ablation modalities [ 14 ]; however, all three patients underwent multiple ablation procedures and the time until post-STAR EAM-guided CA ranged from 32 to 395 days.…”
Section: Discussionmentioning
confidence: 99%
“…However, data on success rates in the emergency situation such as ES are rare [ 2 ]. Additionally, there is an ongoing debate on whether STAR effects predominate in the early or late posttreatment period and whether radiation-induced fibrosis or radiation-induced reprogramming of cardiac conduction contributes to therapy success [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…While cardiac SBRT can technically be performed with current modern stereotactic radiotherapy systems and adequate motion-management strategies [6], the exact radiobiological mechanisms in preexisting fibrosis and arrhythmogenic microenvironments are still not fully understood. Historical and recent preclinical and clinical data suggest that cardiac SBRT at lower doses (20-25 Gy) may induce cardiac conduction reprogramming with increased myocardial contraction while higher doses (> 30 Gy) may induce transmural fibrosis [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%